Study on the Deformation Induced by Vertical Two-Layer Large Diameter Pipe-Jacking in the Soil-Rock Composite Stratum - Guangbiao Shao; Nan Yang; Jianyong Han (Applied Sciences, 2022)
Aiming at the features of deformation caused by large diameter vertical two-layer pipe jacking in the soil-rock composite stratum, on-site monitoring and numerical analysis has been done based on an electric power tunnel project constructed with the pipe jacking method, in which the upper tunnel is located in the soil layer and the lower tunnel is partially located in the rock layer. The research shows that: (1) During upper pipe jacking construction, the maximum transverse and longitudinal ground settlements are about three times those of the lower pipe jacking construction, and the maximum horizontal lateral displacement is about 3.3 times the lower pipe jacking construction. (2) Total ground settlement increases rapidly with the reduction of vertical clear spacing of the upper and lower pipe, and the superimposed effect should be taken into consideration during the vertical arranged pipe-jacking construction. (3) The Peck formula, which is used to estimate lateral surface subsidence distribution, is modified to make it more applicable in the soil–rock composite stratum to calculate the ground settlement induced by the construction of pipe-jacking.